Towards human‐controlled, real‐time shape sensing based flexible needle steering for MRI‐guided percutaneous therapies. Issue 2 (4th August 2016) - Li, Meng; Li, Gang; Gonenc, Berk; Duan, Xingguang; Iordachita, Iulian
Abstract: Background: Accurate needle placement into soft tissue is essential to percutaneous prostate cancer diagnosis and treatment procedures. Methods: This paper discusses the steering of a 20 gauge (G) FBG‐integrated needle with three sets of Fiber Bragg Grating (FBG) sensors. A fourth‐order polynomial shape reconstruction method is introduced and compared with previous approaches. To control the needle, a bicycle model based navigation method is developed to provide visual guidance lines for clinicians. A real‐time model updating method is proposed for needle steering inside inhomogeneous tissue. A series of experiments were performed to evaluate the proposed needle shape reconstruction, visual guidance and real‐time model updating methods. Results: Targeting experiments were performed in soft plastic phantoms and in vitro tissues with insertion depths ranging between 90 and 120 mm. Average targeting errors calculated based upon the acquired camera images were 0.40 ± 0.35 mm in homogeneous plastic phantoms, 0.61 ± 0.45 mm in multilayer plastic phantoms and 0.69 ± 0.25 mm in ex vivo tissue. Conclusions: Results endorse the feasibility and accuracy of the needle shape reconstruction and visual guidance methods developed in this work. The approach implemented for the multilayer phantom study could facilitate accurate needle placement efforts in real inhomogeneous tissues. Copyright © 2016 John Wiley & Sons, Ltd.